Outpatient rituximab, ifosfamide, etoposide (R-IE) in patients older than 60 years with relapsed or refractory diffuse large B-cell lymphoma who are not candidates for stem cell transplantation. Issue 1 (2nd January 2020) - Joshi, Maansi; Taper, John; Forsyth, Cecily; Rowlings, Philip; Campbell, Philip; Crispin, Philip; Harvey, Michael; Underhill, Craig; Bayley, Angela; Byth, Karen; Huang, Gillian; Hertzberg, Mark
Abstract: Patients with relapsed-refractory diffuse large B-cell lymphoma (RR-DLBCL) ineligible for autologous stem cell transplantation (autoSCT) have poor survival. Thirty transplant-ineligible patients older than 60 years were administered rituximab 375 mg/m2 day 1, ifosfamide 1333 mg/m 2 days 1 to 3, and etoposide 80 mg/m 2 days 1 to 3 (R-IE) every 21 days for 6 cycles plus 2 doses of rituximab. Revised international prognostic index 3–4 was seen in 53% and prior rituximab exposure in 60%. The complete and overall response rates were 55% and 76%, respectively. Median progression free survival (PFS) and overall survival were 23 and 24 months, respectively. Patients relapsing within 12 months of prior treatment had a median PFS of 2.5 months compared to 23 months for those relapsing beyond 12 months. Grade 3–4 thrombocytopenia and neutropenia occurred in one and eight patients, respectively. R-IE is an effective, well tolerated regimen in RR-DLBCL patients not fit for autoSCT.